Supervisi, Monitoring, dan Evaluasi Pada Lembaga Sosial SOS Children’s Village, Kota Medan - Aisyah Anggreni; Jubaidah Hasibuan; Jihan Sunita; Nabila Abnulia Lubis; Nurhasanah (Lifelong Education Journal, 2022)
This study aims to identify and describe the results of the Supervision, Monitoring, and Evaluation carried out on educational standards at the SOS Children's Village institution, Medan City. The method used in this research is a qualitative method with a descriptive approach. The results of the research from the supervision of the standards of educators and education staff were found that educators and education staff at SOS Children's Village were known as educators, foster mothers, and aunts who served their souls. Meanwhile, the results of supervision on graduate competency standards are that SOS seeks to prioritize life skills for foster children by having at least 1 life skill, and is facilitated. The results of monitoring the standard of facilities and infrastructure are found that the standard of facilities and infrastructure owned by the SOS institution is categorized as good and maintenance is carried out to keep it in good condition or ready for use. Meanwhile, the results of monitoring of SOS financing standards are sufficient for economic needs to provide a very decent education for foster children. And finally, from the results of the evaluation of the content standards, it was found that SOS Children's Village provided two programs, namely SFC (SOS Family Care) and FSP (Family Strengthening Program). Meanwhile, based on the results of the process evaluation of the SOS Children's Village management that the existing program is running well.